Structural assessment and lateral–torsional buckling design of glass beams restrained by continuous sealant joints. (1st November 2015) - Bedon, Chiara; Belis, Jan; Amadio, Claudio
Highlights: The LTB response of glass beams restrained by continuous sealant joints is investigated. Parametric Finite-Element simulations are presented and discussed under various loading conditions. Closed-form solutions are proposed for the estimation of the critical buckling moment. The effects of partially rigid continuous structural sealants on the global LTB behavior are highlighted. A design buckling curve is proposed for laterally restrained glass beams in LTB. Abstract: Glass is largely used in practice as a structural material, e.g. as beam and plate elements able to carry loads. Their structural interaction is often provided by mechanical connections, although recent trends are moving toward the minimization of metal components and the primary involvement of adhesives or silicone structural joints working as partially rigid continuous restraints. In this work, the lateral–torsional buckling (LTB) behavior of glass beams laterally restrained by continuous silicone joints is assessed. Based on earlier contributions of literature and extended parametric Finite-Element (FE) numerical investigations, closed-form solutions are suggested for the estimation of their Euler's critical buckling moment under various loading conditions. Finally, by means of more detailed incremental nonlinear analyses, their global LTB response is also investigated, to assess their sensitivity to initial geometrical imperfections as well as their prevalent LTB failure mechanism. In conclusion, a generalized buckling design curve able to account for the structural contribution provided by structural silicone joints is proposed for a rational and conservative LTB verification.